Pelatihan manajemen bencana terhadap kesiapsiagaan pada mahasiswa: A literature review - Mufimah, Mufimah; Kamaludin, Ridlwan (Holistik Jurnal Kesehatan, 2025)
Background: Disaster preparedness training has now begun to be developed from elementary to higher education, namely students, with the aim of building a culture of safety and resilience in the younger generation. Universities through the tridharma of higher education have a strategic role in disaster management through learning, research and community service. This role can take place with the active participation of lecturers and students. Purpose: To examine the effect of disaster management training on student preparedness. Method: Literature review research with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach and using PICO. The search databases used were Pubmed/NCBI, Scopus, and Sciencedirect with the keywords "( Student undergraduate) AND (Disaster)) AND (Disaster management training) AND (Disaster Preparedness)". Results: The types of disaster management training consisted of disaster management training, disaster response, first aid education, disaster preparedness, and stages of disaster preparedness and response. The training method used was the same, namely simulation guided by an instructor and the duration of the training varied and tended to be long. The fastest training duration was 30 minutes and the longest was 6 semesters. Conclusion: Disaster management training for students has been proven to be able to improve disaster preparedness, especially in the campus environment.   Keywords: Disaster Management; Higher Education; Students; Training.   Pendahuluan: Pelatihan kesiapsiagaan bencana saat ini sudah mulai dikembangkan mulai dari tingkat pendidikan dasar hingga ke tingkat pendidikan tinggi yaitu mahasiswa dengan tujuan untuk membangun budaya keselamatan dan ketangguhan pada generasi muda. Perguruan tinggi melalui tri dharma perguruan tinggi memiliki peran strategis dalam penanggulangan bencana melalui pembelajaran, penelitian dan pengabdian kepada masyarakat. Peran tersebut dapat berlangsung dengan adanya partisipasi aktif dari dosen dan mahasiswa. Tujuan: Untuk meninjau pengaruh pelatihan manajemen bencana terhadap kesiapsiagaan mahasiswa. Metode: Penelitian literatur review dengan pendekatan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) dan menggunakan PICO. Database pencarian yang digunakan adalah pubmed/NCBI, Scopus, dan Sciencedirect dengan kata kunci "(Student undergraduate) AND (Disaster)) AND (Disaster management training) AND (Disaster Preparedness)". Hasil: Jenis pelatihan penanggulangan bencana terdiri dari pelatihan penanggulangan bencana, tanggap bencana, pendidikan pertolongan pertama, kesiapsiagaan bencana, serta kesiapsiagaan bencana dan tahapan tanggap bencana. Metode pelatihan yang digunakan sama, yaitu simulasi yang dipandu oleh instruktur dan durasi pelatihan bervariasi dan cenderung lama. Durasi pelatihan tercepat adalah 30 menit dan terlama adalah 6 semester. Simpulan: Pelatihan penanggulangan bencana bagi mahasiswa terbukti mampu meningkatkan kesiapsiagaan bencana, khususnya di lingkungan kampus.   Kata Kunci: Mahasiswa; Manajemen Bencana; Pelatihan; Perguruan Tinggi.